Physical education and bodily strengthening on either side of the Rhine: a transnational history of the French bill on physical education and its German reception (1920-1921). Issue 1 (2nd January 2023) - Bolz, Daphné; Saint-Martin, Jean
ABSTRACT: After the Great War, many European countries embarked upon a voluntarist policy to promote physical education and, more broadly, the bodily strengthening of their population. Nevertheless, this movement was marked as much by singular national variations as by the observation of foreign programmes and practices. The aim of this paper is to study the German perception of French initiatives in the light of the fragile Franco-German relations. It analyses a brochure published in 1921 by the Deutscher Reichsausschuss für Leibesübungen (DRA), the most important sports federation under the Weimar Republic. This exceptional 11-page document has an emblematic title: Frankreich und wir! (France and us!) It presents the 1920 French government's bill in favour of bodily strengthening and compares each point with claims made by the German leaders. In this way, it highlights the tireless voluntarism of German sports leaders and the international competition in the development of sports and physical education movements. Finally, this brochure is an exemplary testimony to the development of physical activities according to national models and the growing influence of foreign exemplars in the diffusion of physical education models in connection with national reconstructions. The sources used include historical publications and archives from Germany and France.